Iron chelation with salicylaldehyde isonicotinoyl hydrazone protects against catecholamine autoxidation and cardiotoxicity - Hašková, Pavlína; Kovaříková, Petra; Koubková, Lucie; Vávrová, Anna; Macková, Eliška; Simůnek, Tomáš (Free radical biology & medicine, 2011)
Elevated catecholamine levels are known to induce damage of the cardiac tissue. This catecholamine cardiotoxicity may stem from their ability to undergo oxidative conversion to aminochromes and concomitant production of reactive oxygen species (ROS), which damage cardiomyocytes via the iron-catalyzed Fenton-type reaction. This suggests the possibility of cardioprotection by iron chelation. Our in vitro experiments have demonstrated a spontaneous decrease in the concentration of the catecholamines epinephrine and isoprenaline during their 24-h preincubation in buffered solution as well as their gradual conversion to oxidation products. These changes were significantly augmented by addition of iron ions and reduced by the iron-chelating agent salicylaldehyde isonicotinoyl hydrazone (SIH). Oxidized catecholamines were shown to form complexes with iron that had significant redox activity, which could be suppressed by SIH. Experiments using the H9c2 cardiomyoblast cell line revealed higher cytotoxicity of oxidized catecholamines than of the parent compounds, apparently through the induction of caspase-independent cell death, whereas co-incubation of cells with SIH was able to significantly preserve cell viability. A significant increase in intracellular ROS formation was observed after the incubation of cells with catecholamine oxidation products; this could be significantly reduced by SIH. In contrast, parent catecholamines did not increase, but rather decreased, cellular ROS production. Hence, our results demonstrate an important role for redox-active iron in catecholamine autoxidation and subsequent toxicity. The iron chelator SIH has shown considerable potential to protect cardiac cells by both inhibition of deleterious catecholamine oxidation to reactive intermediates and prevention of ROS-mediated cardiotoxicity.
Keywords: oxidační stres; Binding, Competitive; viabilita buněk; Cell Line; Catecholamines; Enzyme Assays; Hydrazones; reaktivní formy kyslíku; hydrazony; železo; kyselina askorbová; komplexní sloučeniny; Iron Chelating Agents; chelátory železa; Cell Survival; cytoprotekce; Ascorbic Acid; Cytoprotection; Aldehydes; kompetitivní vazba; Caspases; aldehydy; oxidace-redukce; krysa rodu Rattus; Coordination Complexes; kaspasy; Reactive Oxygen Species; katecholaminy; Animals; Iron; myoblasty srdeční; zvířata; Rats; buněčné linie; Myoblasts, Cardiac; Oxidation-Reduction; enzymatické testy; Oxidative Stress